1994
DOI: 10.1515/zna-1994-1116
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the Helical Twist Inversion in Single Component Cholesteric Liquid Crystals

Abstract: The cholesteric twist inversion by temperature variation of a single component thennotropic liquid crystalline system was experimentally investigated and is explained by the partial twistmg power model, evaluating the temperature dependent pilch of five different configurations of a benzoic acid biphenyl ester with two chiral centers. The temperature dependence of the twisting power and the cholesteric pitch for several stereoisomeric compounds can In first appro;timation be predicted by the partial twisting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 2 publications
2
20
0
1
Order By: Relevance
“…The H‐PAs that were synthesized at low (−12 °C) and high (28 °C) temperatures exhibited right‐ and left‐screwed helical senses, respectively, that opposed those of the N*‐LCs required by the polymerization mechanism 37,38. Therefore, the current N*‐LC can produce hierarchically controlled helical structures consisting of the primary to higher‐order structure of H‐PA under thermal stimulus 17–23,39. This is the first report of chiral reaction field with thermally invertible helical sense that has the chemical functions and stability needed to serve as the medium for polymer reactions.…”
mentioning
confidence: 88%
“…The H‐PAs that were synthesized at low (−12 °C) and high (28 °C) temperatures exhibited right‐ and left‐screwed helical senses, respectively, that opposed those of the N*‐LCs required by the polymerization mechanism 37,38. Therefore, the current N*‐LC can produce hierarchically controlled helical structures consisting of the primary to higher‐order structure of H‐PA under thermal stimulus 17–23,39. This is the first report of chiral reaction field with thermally invertible helical sense that has the chemical functions and stability needed to serve as the medium for polymer reactions.…”
mentioning
confidence: 88%
“…In the other, the competition between the different temperature dependencies and opposite chiralities of multiple chiral centers causes the helix inversion 205, 206. Experimental support for the first explanation comes from NLCs doped with chiral dopants,207, 208 whereas results verifying the second explanation use diastereomeric LC compounds 209, 210…”
Section: Going Beyond the Reflectance Limitmentioning
confidence: 99%
“…Nevertheless, it becomes apparent that all of these molecules incorporate at least two chiral elements, often chiral centers. It has been shown that the cholesteric twist inversion of single component systems can be explained by a superposition of the influences of each chiral center [39,40]. At last, of special interest are the optical properties of cholesteric phases.…”
Section: Propertiesmentioning
confidence: 99%